Emergency contraceptive knowledge, attitudes and practices among female students at the University of Botswana: A descriptive survey - Bobby Kgosiemang; Julia Blitz (AOSIS, 2018)
Background: Unintended pregnancies are associated with unsafe abortions and maternal deaths, particularly in countries such as Botswana, where abortion is illegal. Many of these unwanted pregnancies could be avoided by using emergency contraception, which is widely available in Botswana. Aim: To assess the level of knowledge, attitudes and practices of female students with regard to emergency contraception at the University of Botswana. Setting: Students from University of Botswana, Gaborone, Botswana. Methods: A descriptive survey among 371 students selected from all eight faculties at the university. Data were collected using a self-administered questionnaire and analysed using the Statistical Package for Social Sciences. Results: The mean age was 20.6 years (SD 1.62), 58% were sexually active, 22% had used emergency contraception and 52% of pregnancies were unintended. Of the total respondents, 95% replied that they had heard of emergency contraception; however, only 53% were considered to have good knowledge, and 55% had negative attitudes towards its use. Students from urban areas had better knowledge than their rural counterparts (p = 0.020). Better knowledge of emergency contraception was associated with more positive attitudes towards actual use (p < 0.001). Older students (p < 0.001) and those in higher years of study (p = 0.001) were more likely to have used emergency contraception. Conclusion: Although awareness of emergency contraception was high, level of knowledge and intention to use were low. There is a need for a targeted health education programme to provide accurate information about emergency contraception.